The Significance of Community Capital in Generating and Upholding a Local Food Movement - Persson, Carly (My University, 2017)
This study uses a qualitative approach to investigate factors motivating restaurant owners in Oshkosh, Wisconsin, to source their menu items locally and, secondly, farmers around Oshkosh to provide them with products. I initially hypothesized that the connection between the supply of goods from farmers and restaurant owners primarily stems from profit but found after non-random interviews with four restaurant owners and three farmers from the region that the profit pursuit thesis is invalid. For my research purposes, local is defined as coming from within a 60-mile radius. Food is a foundational component of daily life, and with it comes specific ritual and behavior, which can be studied through a sociological lens. Through face-to-face, semi-structured interviews with stakeholders in Oshkosh’s local food movement, I shed light on various themes including: emphasis on community, instances of false advertising, socioeconomic status of restaurant clientele, accessibility of local farmers to restaurant owners, the future of the local food movement, and variation in local product percentages among restaurants. More research should be done on this topic in general and more specifically in the Fox River Valley region of Wisconsin.
Oshkosh Scholar, Volume XI
Keywords: Local food movements; Restaurants; Local food sources; Farming